Programmed death-ligand1 is a determinant of recurrence in alveolar echinococcosis - Gaëtan-Romain Joliat; Sebastiao N. Martins-Filho; Simon Haefliger; Nicolas Demartines; Nermin Halkic; Ismail Labgaa; Christine Sempoux (International Journal of Infectious Diseases, 2023)
Objectives: Alveolar echinococcosis (AE) recurrence is one of the major stakes in patients undergoing surgery, the main curative treatment. Preliminary data demonstrated an effect of programmed death-ligand1 (PD-L1) inhibitors on AE proliferation in animals. The current study aimed to analyze the prognostic value of PD-L1 expression in tissue samples of patients with AE undergoing surgery. Methods: A cross-sectional study of patients operated for AE between 2002 and 2017 was performed. Patients with recurrence were matched 1: 2 with patients without recurrence. The matching criteria were PNM staging (P = hepatic localization of the parasite, N = extra-hepatic involvement of neighboring organs, and M = absence or presence of metastasis), resection status, preoperative albendazole treatment, and lesion size. PD-L1 immunohistochemistry staining was performed in surgical liver specimens. The expression of PD-L1 was assessed in immune cells. Disease-free survival was calculated using the Kaplan-Meier method. Results: Among 68 consecutive patients, eight patients with recurrence were matched to 16 patients without recurrence. PD-L1 was overexpressed in patients with recurrence (recurrence: PD-L1 <1%: one, PD-L1 ≥1%: seven; no recurrence: PD-L1 <1%: nine, PD-L1 ≥1%: seven, P = 0.040). Moreover, patients with lower PD-L1 expression (<1%) showed better median disease-free survival (120 months, 95% confidence interval 104-135 vs 74, 95% confidence interval 44-104, P = 0.050). Conclusion: These findings highlight the proof of concept of PD-L1 in AE, but further data on its prognostic importance and the role of immune checkpoint blockade as a promising therapeutical strategy are needed.